Pengaruh Konsentrasi Awal Larutan Ion Logam Cd2+ terhadap Penyerapan Biomassa Kulit Langsat (Lansium domesticum) yang Dimodifikasi Metanol - Ideal, Flami Luthfianisa; Kurniawati, Desy (Lembaga Yasin AlSys, 2023)
Industrial activities have been growing rapidly lately. Increased industrial activity can improve the quality of human life, but behind it there are adverse effects on the environment and human health. There are many harmful heavy metals found in industrial waste. One of them is cadmium metal, which is one of the dangerous heavy metals that if accumulated in the body can threaten human health. Langsat fruit peel waste can be utilized as an adsorbent. Adsorbent is an absorbent substance/material to absorb heavy metal ions. Biomass was characterized using AAS instrument to determine the concentration of Cd2+ metal ion absorption in langsat peel biomass. This study was conducted to determine the effect of the initial concentration of solution on the absorption of Cd2+ metal ions in methanol-modified langsat peel biomass. The results showed that the optimal absorption of Cd2+ metal ions in methanol-modified langsat peel biomass was at a concentration of 400 mg/L with an absorption capacity of 9.387 mg/g.